Residual and Recurrent Disease Following Endoscopic Endonasal Approach as a Reflection of Anatomic Limitation for the Resection of Midline Anterior Skull Base Meningiomas. Issue 4 (9th July 2021) - Setty, Pradeep; Fernandez-Miranda, Juan C; Wang, Eric W; Snyderman, Carl H; Gardner, Paul A
Abstract: BACKGROUND: Endoscopic endonasal approaches (EEAs) to anterior skull base meningiomas have grown in popularity, though anatomic limitations remain unclear. OBJECTIVE: To show the anatomic limits of EEA for meningiomas. METHODS: Retrospective chart review for all patients that underwent EEA for anterior skull base meningiomas from 2005 to 2014. RESULTS: A total of 100 patients averaged follow-up of 46.9 mo (24-100 mo). A total of 35 patients (35%) had olfactory groove, 33 planum sphenoidale (33%), and 32 tuberculum sella (32%) meningiomas. The average diameter was 2.9 cm (0.5-8.1 cm). Vascular encasement was seen in 11 patients (11%) and calcification in 20 (20%). Simpson Grade 1 (SG1) resection was achieved in 64 patients (64%). Only calcification impacted degree of resection (40% SG1, P = .012). The most common residual was on the anterior clinoid dura (11 patients [11%]). Six (6%) had residual superior/lateral to the optic nerve. Residual tumor was adherent to the optic apparatus or arteries in 5 patients (5%) each, and 3 patients (3%) had residual lateral to the mid-orbit. Rates of residual decreased over time. A total of 11 patients (11%) had tumor recurrence (mean of 40 mo): 4 (4%) on the anterior clinoid, 2 (2%) each on the lateral orbital roof, adherent to optic apparatus and superolateral to the optic nerve, and 1 (1%) was at the anterior falx. CONCLUSION: Anterior skull base meningiomas can effectively be approached via EEA in most patients; tumors extending to the anterior clinoid, anterior falx, or superolateral to the optic nerve or orbital roof, especially if calcified, may be difficult to reach via EEA.